The Role Of Parents In The Mental Recovery Of Children In Conflict With The Law - Mitro Subroto; Muhamad Apri Hidayat (Universitas Merdeka Madiun, 2025)
Abstract Introduction to the Problem: Children in conflict with the law often experience psychological distress, including feelings of guilt, shame, and social exclusion. Parental support plays a crucial role in their mental recovery, but parents also face challenges such as societal stigma and pressure, which may impact their ability to provide effective emotional support. Purpose/Study Objectives: This study aims to explore the role of parents in the mental recovery of children in conflict with the law and to understand the challenges parents face in providing support. Design/Methodology/Approach: A qualitative research approach was employed using in-depth interview techniques. The study involved 10 parents whose children have been involved in legal cases, allowing for an in-depth exploration of their experiences and perspectives. Findings: The study found that emotional support from parents is crucial in helping children cope with guilt and shame while encouraging them to focus on a better future. However, parents often struggle with social stigma and pressure from their surroundings, which can affect their ability to provide support. The findings highlight that the active involvement of parents in the rehabilitation process, along with community support, plays a vital role in the mental recovery of children in conflict with the law. These insights can help practitioners and policymakers develop more effective intervention programs for both children and their families. Paper Type: Research Article